The Influence of Transformational Leadership and Perceived Organizational Support on Employee Engagement: The Mediating Role of Job Satisfaction Among Employees of Bpjamsostek Regional Office of Southern Sumatra - Ahmad Farhan; Wita Farla; Yomeini Margareth (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of transformational leadership and perceived organizational support on employee engagement, with job satisfaction as a mediator, among employees of BPJamsostek's Southern Sumatra Regional Office. Using quantitative explanatory design, data collected from 243 non-structural employees through a census were analyzed using PLS-SEM. Results show that transformational leadership, perceived organizational support, and job satisfaction positively and significantly affect employee engagement. Transformational leadership and perceived organizational support significantly improve job satisfaction, which partially mediates both relationships. These findings support Social Exchange Theory and identify supportive leadership, organizational support, and job satisfaction as key drivers of employee engagement. Keywords: Transformational Leadership; Perceived Organizational Support; Job Satisfaction; Employee Engagement; Social Exchange Theory